The Pursuit to Develop a Theoretical Approach to Obtaining Multicultural Autonomy in Agricultural and Extension Education - Stacy K Vincent; Donna M. Westfall-Rudd (Journal of International Agricultural and Extension Education, 2025)
A lot goes into the development of an individual’s identity. Cultural beliefs and the cultural milieu of one’s story-lined upbringing establish the foundation that allows for the unique development of an individual and to whom that individual can naturally connect. The learner receives positive, negative, or stagnant growth based on their teacher’s cultural development. The purpose of this philosophical manuscript is to synthesize the development of self by the provenances that define an educator’s comfortability level and an approach to expanding provenances to reach a homogenous learning community that can positively outturn the agriculture industry and the education profession. A concept coined Multicultural Autonomy and Multicultural Autonomous Agricultural Educator is introduced to provide a foundation for assisting post-secondary students and adults in obtaining the necessary skills to teach a growing population of diverse learners.
Keywords: Awareness; Communal Orientation; Provenances; Autonomous; Self-Identity; Cultural Discovery